Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Powtoon Terhadap Keterampilan Berpikir Kritis Peserta Didik Kelas XI SMA Materi Sistem Gerak - Mamta Humairoh; Nirwana Anas; Sayed Akhyar (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to determine the effect of the problem based learning model assisted by Powtoon media to improve the critical thinking skills of class XI students at SMAN 11 Medan on motion systems material. This research is quantitative research. This research used a quasi-experimental method with a population of 251 class XI Science students consisting of 7 groups. Sampling used cluster random sampling, consisting of the experimental class and control class, each with 36 students. The data collection instrument was a description test with 5 questions which were then analyzed using the t test. The results of hypothesis testing using SPSS version 24 software obtained Sig < α, namely 0.0001 < 0.05 so that H0 was rejected and H1 was accepted. This shows that there is an influence of the Problem Based Learning (PBL) model on students' critical thinking skills.